National, Imperial, Colonial and the Political: British Imperial Histories and their Descendants - Syriatou, Athena (Historein, 2013)
This paper discusses the pivotal moments of British imperial history from the eighties to today after a brief reference to the study of imperial history since the beginning of historical writing as a discilpline. It refers selectively to discussions as well as to books and attempts to exhibit in each period the works which characterise the general arguments, the perceptions of ideas by the academic environment and the historiographical issues examined.